2022
DOI: 10.1101/2022.09.26.509230
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experience-dependent flexibility in a molecularly diverse central-to-peripheral auditory feedback system

Abstract: Brainstem olivocochlear neurons (OCNs) modulate the earliest stages of auditory processing through feedback projections to the cochlea and have been shown to influence hearing and protect the ear from sound-induced damage through unclear mechanisms. Here, we used single-nucleus sequencing, anatomical reconstructions, and electrophysiology to characterize OCNs during postnatal development and after sound exposure. We identified markers for known OCN subtypes, medial (MOC) and lateral (LOC) OCNs, and show that t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 121 publications
0
1
0
Order By: Relevance
“…The larger ABR Wave I amplitudes and larger ASR amplitudes suggest compensation and/or hyperreactivity in α9α10KO mice. One potential mechanism for preserving hearing function in α9α10KO mice is activity-dependent plasticity in the lateral olivocochlear efferents (Frank et al, 2022; Niu & Canlon, 2002; Wu et al, 2020). A previous study reported qualitatively normal ChAT staining of lateral olivocochlear synapses in α9α10KO mice (Morley et al, 2017; not quantified), but changes in other neurotransmitter systems have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The larger ABR Wave I amplitudes and larger ASR amplitudes suggest compensation and/or hyperreactivity in α9α10KO mice. One potential mechanism for preserving hearing function in α9α10KO mice is activity-dependent plasticity in the lateral olivocochlear efferents (Frank et al, 2022; Niu & Canlon, 2002; Wu et al, 2020). A previous study reported qualitatively normal ChAT staining of lateral olivocochlear synapses in α9α10KO mice (Morley et al, 2017; not quantified), but changes in other neurotransmitter systems have not been investigated.…”
Section: Discussionmentioning
confidence: 99%